(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2024)
Since September 7, 2017, the two English-speaking regions of Cameroon have been brutalised by a separatist struggle variously called the Ambazonia War, the NOSO war or the Anglophone crisis. This conflict which opposes some separatist armed groups and government forces has involved the use by each side, of online-based visual propaganda aimed at framing their opponents in a negative light and wooing both domestic audiences and the international community in favour of their respective causes. This determination to negatively frame the opposite camp has led not only to a war of gloomy images but also the recrudescence of an aesthetic of violence in the video-assisted propaganda of the warring parties. This aesthetics of violence has so far remained understudied. This paper seeks to fill this gap by examining how specific violent images have circumstantially been constructed, deconstructed and mobilised by both separatist and anti-separatist forces in this conflict to frame or counter-frame their opponent. Using a qualitative content analysis of relevant online videos/footage, semiotics, documentary analysis and critical observations, the paper specifically addresses three questions: What has been the role of visual-based propaganda in the Ambazonia war? How have the domestic and the foreign audiences received this visual propaganda? And how have international observers – such as news agencies, politics observatories and other world organisations – mediated in the war of images that opposes government and the armed separatist groups in Cameroon?